DEVELOPMENT AND VALIDATION OF RP-HPLC METHOD FOR THE ESTIMATION OF DOLUTEGRAVIR AND RILPIVIRINE IN BULK AND PHARMACEUTICAL DOSAGE FORM AND ITS APPLICATION TO RAT PLASMA - B, VEERASWAMI; VMK, NAVEEN (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The present paper describes a simple, accurate, and precise reversed-phase high-performance liquid chromatography (HPLC) method for rapid and simultaneous quantification of dolutegravir (DTG) and rilpivirine (RPV) in bulk and pharmaceutical dosage form and rat plasma. Methods: The chromatographic separation was achieved on Phenomenex C18 (150x4.6mm, 5μm). Mobile phase contained a mixture of 0.1% Ortho phosphoric acid and acetonitrile in the rato of 60:40 v/v, flow rate 1.0ml/min and ultraviolet detection at 262nm. Results: The retention time of DTG and RPV was 4.35 min and 7.73 min, respectively. The proposed method shows a good linearity in the concentration range of 10–150 μg/ml for DTG and 5–75 μg/ml for RPV under optimized conditions. Precision and recovery study results are in between 98 and 102%. In the entire robustness conditions, percentage relative standard deviation is <2.0%. Degradation has minimum effect in stress condition and solutions are stable up to 24 h. DTG and RPV drugs are release 98% at 2 h in rat body. Conclusion: This method is validated for different analytical performance parameters like linearity. Precision, accuracy, limit of detection, limit of quantification, robustness, and pharmacokinetic study were determined according to the International Conference of Harmonization (ICH) Q2B guidelines. All the parameters of validation were found in the acceptance range of ICH guidelines. The same method is also applied for plasma samples study in bioanalytical work.